2020
DOI: 10.1177/1368430220962179
|View full text |Cite
|
Sign up to set email alerts
|

The psychological antecedents of resistance to humanitarian aid

Abstract: Victims of natural or humanitarian disasters sometimes resist aid offered to them, resulting in slower recovery among victims, and feelings of rejection among aid offerers. We present two studies conducted in Indonesia that investigated motives for spurning offers of humanitarian aid. Both studies showed that beliefs in developed countries’ conspiracies lead participants to see humanitarian aid as guided by strategic rather than prosocial motives. Perceived strategic motives in turn enhanced aid resistance, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 58 publications
(85 reference statements)
0
12
0
Order By: Relevance
“…The main effects observed in our studies were at least partially accounted for by concern about the in-group’s reputation. Similarly, past studies linked national narcissism to refusing aid from others due to suspected ulterior or strategic motives of those offering help ( Mashuri et al, 2020 ). Those high in national narcissism, therefore, seem to be willing to refuse benefits to their in-group based on unfounded claims ( Cislak et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main effects observed in our studies were at least partially accounted for by concern about the in-group’s reputation. Similarly, past studies linked national narcissism to refusing aid from others due to suspected ulterior or strategic motives of those offering help ( Mashuri et al, 2020 ). Those high in national narcissism, therefore, seem to be willing to refuse benefits to their in-group based on unfounded claims ( Cislak et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Those high in collective narcissism may also forgo help from outsiders. A study by Mashuri and colleagues (2020) demonstrated that national narcissism in Indonesia was related to refusing humanitarian aid from developed countries. The effect was driven by conspiracy beliefs about malignant intentions behind the offer as well as the perception that accepting humanitarian aid would damage the in-group’s reputation.…”
Section: Sacrificing the In-group To Defend Its Imagementioning
confidence: 99%
“…From the point of view of social wellbeing, what seems important are the relations between CBs and various unfavorable attitudes, such as anti-science attitudes ( Marques et al, 2022 ), climate skepticism ( Hornsey et al, 2018a ), lower prosocial orientation ( Hornsey et al, 2021 ), resistance to humanitarian aid ( Mashuri et al, 2022 ), pharmacophobia ( Petelinšek and Lauri Korajlija, 2020 ), negative attitudes toward HIV testing ( Patev et al, 2019 ; Hood et al, 2020 ), and other socially unfavorable attitudes ( Jedinger, 2021 ; Molz and Stiller, 2021 ). The implications of CBs potentially affecting social communication include: endorsement of fake news ( Anthony and Moulding, 2019 ; Halpern et al, 2019 ; Faragó et al, 2020 ; Frischlich et al, 2021 ), rating nonsense as profound ( Čavojová et al, 2019 ), and a willingness to share conspiracy theories online ( Lobato et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, collective narcissism in extremist organizations representing ethnic and religious minorities is associated with acceptance of terrorist violence against the powerful majorities [40]. Moreover, collective narcissism in disadvantaged groups is associated with distrust and conspiracy theories about the more powerful groups leading to rejection of their aid to advance the disadvantaged ingroup [41].…”
Section: Collective Delusions That Render Violence a 'Logical Conclus...mentioning
confidence: 99%